Interdependence among nine asian stock markets before & during the Asian economic crisis. - Ong, Cindy Jing Yin. (2008)
This paper looks at the linkages among the major Asian stock markets before and during the Asian Economic Crisis to determine the diversification benefits to be gained by investors in the Asian region in times of economic turmoil.